Liver infiltrating T lymphocytes express interferon γ and inducible nitric oxide synthase in chronic hepatitis C virus infection. Issue 2 (1st February 2000) - Schweyer, S; Mihm, S; Radzun, H J; Hartmann, H; Fayyazi, A
Abstract : BACKGROUND: Pathogenesis of hepatitis C virus (HCV) associated liver injury is thought to be due to the host antiviral immune response. Using a quantitative, competitive RT-PCR technique, we recently showed that expression of interferon γ (IFN-γ) and IFN-γ inducible type of nitric oxide synthase (iNOS) is increased in homogenised liver tissue of patients with chronic HCV infection. AIMS: To determine the cellular origin of IFN-γ and iNOS expression and to examine the hypothesis that T cell derived IFN-γ secretion induces iNOS in hepatocytes in chronic HCV infection. METHODS: By applying a non-radioactive in situ hybridisation method combined with indirect immunofluorescence, 33 liver biopsy specimens from patients with chronic HCV infection were studied for cellular expression of IFN-γ and iNOS mRNA. RESULTS: In chronic HCV infection, both IFN-γ and iNOS gene expression were significantly increased. IFN-γ and iNOS mRNA were observed in CD3+ lymphocytes infiltrating portal tracts and hepatic lobules, but not in hepatocytes. CONCLUSIONS: Results are consistent with previous reports that IFN-γ and iNOS transcripts are elevated in chronic HCV infection. In contrast to the hypothesis, IFN-γ expressing T cells do not induce iNOS in hepatocytes, but probably in T cells. T lymphocytes expressing IFN-γ and/or iNOS have the potential to participate in autocrine and paracrine pathways that may contribute to the pathobiology of chronic hepatitis C.